Biomass and Carbon Storage Estimation of Melaleuca Forests in Thanh Hoa District, Long An Province - Nguyen, Lu Phuong; Ly, Nhat Tan; Tran, Anh Tu (Journal of Technical Education Science, 2025)
Forests play an important role in living on Earth by absorbing and storing carbon dioxide (CO2), emitting oxygen for the atmosphere, and human life. Forests can digest about 1/12 of the CO2 in the atmosphere and storage of about 72% of the total carbon in global sinks. Forest carbon credits are considered an important tool in reducing carbon emissions and global warming potential. This study aims to estimate the biomass and carbon storage of Melaleuca plantations in Thanh Hoa district, Long An province, Vietnam. The findings contribute to developing sustainable forest management mechanisms and carbon credit markets. Nine standard plots (10x10m) were established to collect data on number of tree, diameter at breast height, and select trees. The results showed that carbon storage (CO2) was 689.13 kg/standard plot for 2-year-old Melaleuca forests and 2423.5 kg/standard plot for 6-year-old Melaleuca forests. The study provides valuable information for forest managers and policymakers in promoting sustainable Melaleuca forest management and carbon credit trading.